Embedded Ultrasonic Inspection of Liquid Filled Pressure Vessels - (:unkn) unknown (My University, 2023)
Structural health monitoring and ultrasonic inspection techniques can be used to inspect a structure for degradation. There are several different approaches for doing this including the use of an embedded sensing system which uses elastic wave propagation through the structure. Previous work using this method has explored ultrasonic inspection of a simple, flat plate structure, however, structures often have more complex geometry, and the flat plate offers only a basic understanding of elastic wave propagation. Therefore, experimental approaches and results drive how these techniques can be used for ultrasonic inspection of complex vessels where challenges arise due to the potential for multiple elastic wave propagation modes and paths through the complex geometry combined with effects of changing environment conditions. Research here investigates the fundamental capability of using embedded ultrasonic inspection techniques on a complex pressurized water tank structure using the previously established methods for basic structures. The investigation uses permanently mounted lead zirconate titanate piezoelectric transducers to actuate and sense ultrasonic waves propagating through the tank structure. The change in wave propagation is explored through the simulated damage of a magnet placed on the structure, filling the tank, and pressurizing the tank. The results of this work are intended to provide a basis and physics-based understanding upon which to build capabilities of structural health monitoring of liquid filled pressure vessels to detect and locate degradation under different environmental and state effects. Liquid filled pressure vessels are common in modern life, from the water heaters in our homes to the fuselage of a spacecraft. Failure of liquid filled pressure vessels can have severe consequences resulting in direct damage due to liquid release, as well as the consequences of system failure and downtime. Therefore, the use of structural health monitoring based on embedded ultrasonic systems has the potential to significantly impact the safety and reliability of a system and to save resources spent in maintenance and downtime with its ability to detect, locate, characterize, and quantify degradation of a structure.
Keywords: embedded; nondestructive evaluation; pressure vessels; PZT; structural health monitoring; Ultrasonic